Olympic hosting in Canada - Promotional ambitions, political challenges - Whitson, D. (SIRC Newsletter, 2008)
David Whitson examines Olympic Games hosting (bids and event management) from the perspective of ideology, mass media, politics and economic forces (globalization). The Montreal Olympics (1976), the Calgary Olympics (1988) and the upcoming Vancouver Olympics (2010) are used to illustrate his arguments. Topics covered include: the Olympic Games as a mass media event of global scope; internationalism versus globalism; the Olympics as a defining moment in the life of a city; the "business" approach, as exemplified by Calgary.